PERFORMANCE ANALYSIS OF A HIGH-GAIN BIDIRECTIONAL DC-DC CONVERTER FED EV DRIVE WITH SLIDING MODE CONTROLLER FOR REDUCED RIPPLE DISTORTION - Mr. Undaveli Govardhan Reddy; Mr. B. Venu Reddy Kumar; Dr. Velappagari sekhar; Ms. K. Renuka (Utilitas Mathematica, 2024)
This research presents an advanced high-gain bidirectional DC-DC converter (BDC) for electric vehicle (EV) drive applications, incorporating a sliding mode controller (SMC) to minimize ripple distortion and enhance system performance. The proposed non-isolated converter integrates an energy storage system efficiently, achieving high voltage gain without the need for voltage multiplier cells (VMC) or hybrid switched-capacitor techniques. The converter utilizes a dual current path inductor structure, reducing component size while eliminating additional clamping circuits. The EV drive system operates in both forward motoring and regenerative braking modes, ensuring optimal energy utilization. During motoring mode, the converter supplies power from the battery to the motor, whereas, in braking mode, the motor functions as a generator, transferring recovered energy back to the battery. By incorporating an SMC, the system exhibits superior dynamic response, reduced voltage and current ripple, and enhanced robustness against parameter variations and external disturbances. The proposed system is simulated using MATLAB/Simulink and OPAL-RT Software-in-Loop(SIL) environment to analyze its performance under different driving conditions. Comparative results validate that the SMC-based control significantly improves power quality, ensuring stable and efficient operation of the EV drive system. This approach offers a reliable solution for high-performance EV applications with efficient energy recovery during braking.